2008
DOI: 10.1002/rmv.592
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenesis by retroviruses: old and new paradigms

Abstract: Retroviruses are associated with a variety of diseases including an array of malignancies, immunodeficiencies and neurological disorders. In particular, studies of oncogenic retroviruses established fundamental principles of modern molecular cancer biology. Studies of avian Rous sarcoma virus (RSV) led to the discovery of the viral oncogene src, and this was followed by the discovery of other viral oncogenes in retroviruses of mammals including rodents, cats, monkeys and so forth. Studies of the viral oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 154 publications
0
80
0
1
Order By: Relevance
“…Therefore, density gradients, which are often used to separate EVs from contaminating protein aggregates on the basis of differences in buoyant densities (40), are not always reliable for separation of EVs from viral particles. Similar technical hurdles were also experienced at the early stages of retrovirus research, when there were long-lasting disagreements and controversies regarding replication-incompetent oncoviral particles causing cancer and their dependence on competent helper viruses for propagation (41). In those early days, electron microscopists observed that ultracentrifuged viruses copelleted with other 100-nmsized membrane-enclosed particles.…”
Section: Mission (mentioning
confidence: 84%
“…Therefore, density gradients, which are often used to separate EVs from contaminating protein aggregates on the basis of differences in buoyant densities (40), are not always reliable for separation of EVs from viral particles. Similar technical hurdles were also experienced at the early stages of retrovirus research, when there were long-lasting disagreements and controversies regarding replication-incompetent oncoviral particles causing cancer and their dependence on competent helper viruses for propagation (41). In those early days, electron microscopists observed that ultracentrifuged viruses copelleted with other 100-nmsized membrane-enclosed particles.…”
Section: Mission (mentioning
confidence: 84%
“…Before the discovery of HTLV-1, many oncogenic retroviruses have been found, which induce malignant tumors in animals such as avian and rodent (Maeda et al, 2008). Most animal oncogenic retroviruses carry oncogenes, but they are totally different from the HTLV-1 oncogene for Tax1.…”
Section: Resultsmentioning
confidence: 99%
“…ALV, a member of the genus Alpharetrovirus of the family Retroviridae, can also acquire cellular oncogenes by recombination events during the infection process, producing ATVs with the ability to induce transformation in some specific types of cultured cells and to rapidly induce tumour formation in chickens within 2 weeks (Maeda et al, 2008;Vogt, 2012). To date, dozens of naturally occurring ATVs coding for different viral oncogenes -such as src, fps, myc, myb, jun and ros -have been isolated (Martin, 2001;Vogt, 2012;Wang & Hanafusa, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Some ALV strains can obtain cellular oncogenes (c-onc) from host cells by homologous recombination events during infection to become 'acutely transforming viruses' (ATVs), which have the ability to rapidly induce tumour formation in chickens over a period of only a few weeks and can transform some specific cell types in vitro (Maeda et al, 2008). However, most ATVs are replication defective and can replicate only when replication-competent viruses are present to serve as 'helper viruses'.…”
Section: Introductionmentioning
confidence: 99%